2022
DOI: 10.1063/5.0066151
|View full text |Cite
|
Sign up to set email alerts
|

Design of a high-performance centrifugal compressor impeller and an investigation on the linear effects of the hub

Abstract: The performance of the turbocharger can be improved by optimizing the structural parameters of the compressor impeller. In this work, the existing centrifugal compressor impeller was taken as the case study, and the line shape of the hub was modified in order to study the influence of the line curvature of the hub on the compressor performance. Furthermore, the Navier–Strokes flow equation and the fourth-order Runge–Kutta method were used with Numeca software in order to solve the steady-state RANS equation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Root Mean Square Error (RMSE): This is a measure of the standard deviation of actual results of CFD analysis from the ANN-predicted results and is given by Equation (13). It describes the spread of predicted results around the regression line.…”
Section: Key Performance Indices For Ann Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Root Mean Square Error (RMSE): This is a measure of the standard deviation of actual results of CFD analysis from the ANN-predicted results and is given by Equation (13). It describes the spread of predicted results around the regression line.…”
Section: Key Performance Indices For Ann Studymentioning
confidence: 99%
“…Yang et al [13] used a centrifugal compressor impeller in their case study, and the line shape of the hub was changed to investigate the effect of line curvature on compressor performance. The numerical research findings revealed that within the design value range, the curvature of the impeller hub profile increased as the flow range and surge margin of the compressor impeller increased.…”
Section: Introductionmentioning
confidence: 99%
“…This would reduce mechanical efficiency. Zhao et al [19] analyzed the influence of blade shape [20] on pressure oscillations in the flow field [21]. They made improvements to the design of the blades.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al studied a set of high-speed compressor impellers with different geometries and analyzed the secondary flow model, where the ratio of impeller inlet diameter to outlet diameter has an effect on the impeller flow uniformity, which, in turn, affects the compressor efficiency [23]. Yang et al modified the hub alignment to investigate the effect of hub curvature on the performance of the compressor [24]. Hong et al, through numerical simulations of a centrifugal compressor for a hydrogenpowered fuel electric vehicle, found that the generation of leaf top leakage, hub separation, and horseshoe vortex structure determined the degree of the aerodynamic performance of the centrifugal compressor [25].…”
Section: Introductionmentioning
confidence: 99%